Composite material concrete, concrete pole and preparation method of concrete pole

By composite modification of the regenerated aggregate and combining reinforced fibers, the problem of insufficient mechanical properties of the cement pole containing regenerated aggregate is solved, and the effect of improving compressive strength and improving crack and bending properties is achieved, and the preparation cost is reduced.

CN119661155APending Publication Date: 2025-03-21GUANGDONG GUANGZE IND CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411852371.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Cement poles containing recycled aggregates have many problems in mechanical properties. The existing improvement measures are costly and have poor results, making it difficult to promote on a large scale.

Method used

Using the technical solution of composite concrete, by mixing calcined concave and convex rod soil, metakaolin, quicklime, sodium carbonate and silane coupling agent with recycled aggregates, and combining reinforced fibers, the adverse effects of recycled aggregates on concrete are reduced at the same water-cement ratio, and the compressive strength is improved and the crack resistance and bending resistance are improved.

Benefits of technology

With the same water-cement ratio, the compressive strength of the concrete is improved, and the crack resistance and bending resistance of the cement pole made of the concrete is improved, the preparation cost is reduced, and the cost-effectiveness is higher.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190916260000081
    Figure BDA0005190916260000081
  • Figure BDA0005190916260000091
    Figure BDA0005190916260000091
Patent Text Reader

Abstract

The invention discloses composite material concrete, a concrete pole and a preparation method of the concrete pole, and relates to the technical field of concrete. The invention relates to composite material concrete, which is prepared from 280 to 300 parts of cement, 120 to 160 parts of coal ash, 400 to 500 parts of composite recycled aggregate, 750 to 850 parts of natural coarse aggregate, 500 to 550 parts of fine aggregate, 0.6 to 1 part of reinforcing fiber, 2.6 to 3.04 parts of composite water reducing agent and 160 to 180 parts of water II, the composite recycled aggregate is prepared by mixing and modifying the recycled aggregate with calcined attapulgite, metakaolin, quick lime, sodium carbonate and a silane coupling agent. The recycled aggregate is subjected to composite modification and is matched with the reinforcing fiber, so that under the condition of the same water cement ratio, the adverse effect of the recycled aggregate on the concrete can be reduced to a certain extent, the compressive strength of the concrete can be effectively improved, and meanwhile, the crack resistance and bending resistance of a cement pole made of the concrete can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a composite material concrete and cement pole and a preparation method thereof. Background Art

[0002] As an important supporting part of power transmission lines, cement poles play an irreplaceable role in modern urban construction and development. Traditional cement poles are mainly made of concrete and steel bars or steel wires through a centrifugal molding process. The molding principle is to use a high-speed rotating centrifuge to drive the steel mold to rotate, and use the centrifugal force to make the concrete in the steel mold fully dense, and finally form the annular cavity structure of the pole. This molding method makes the cement pole have a certain strength and durability, which provides an important guarantee for the stable operation of the power system.

[0003] In actual applications, most manufacturers will add a small amount of recycled aggregate to cement poles to replace natural aggregate in order to reduce the production cost of cement poles. However, this will cause many problems in the mechanical properties of cement poles. With the advancement of new material science, the application of various modifiers and reinforcing fibers can make up for the mechanical properties of cement poles containing recycled aggregates to a certain extent. However, these improvement measures are not only costly, but also have low improvement effects, making them difficult to promote and use on a large scale. Summary of the invention

[0004] In order to increase the mechanical strength of cement poles containing recycled aggregates and improve the comprehensive performance of cement poles, the present application provides a composite material concrete and cement pole and a preparation method thereof.

[0005] In the first aspect, the present application provides a composite material concrete adopting the following technical solution: A composite material concrete comprises the following raw materials in parts by weight: Cement: 280-300 parts; Fly ash: 120-160 parts; Composite recycled aggregate: 400-500 parts; Natural coarse aggregate: 750-850 parts; Fine aggregate: 500-550 parts; Reinforcing fiber: 0.6-1 part; Composite water reducing agent: 2.6-3.04 parts; Water II: 160-180 parts; The composite recycled aggregate is prepared by mixing and modifying recycled aggregate with calcined attapulgite, metakaolin, quicklime, sodium carbonate and silane coupling agent, and the recycled aggregate is obtained by crushing and screening waste concrete.

[0006] By adopting the above technical scheme, the recycled aggregate is modified by calcined attapulgite, metakaolin, quicklime, sodium carbonate and silane coupling agent, and combined with reinforcing fiber, under the condition of the same water-cement ratio, the adverse effects of the recycled aggregate on the concrete can be reduced to a certain extent, and the compressive strength of the concrete can be effectively improved. At the same time, it is also beneficial to improve the crack resistance and bending resistance of the cement pole made of the concrete.

[0007] Optionally, the method for preparing the composite recycled aggregate comprises the following steps: A1. The waste concrete is fully crushed, cleaned, impurity-removed and sieved to obtain a recycled aggregate with a particle size of less than 20 mm; the attapulgite is continuously calcined at 450-500° C. for 1-2 hours, and then the heating is stopped and the attapulgite is naturally cooled to room temperature to obtain calcined attapulgite; the recycled aggregate is fully mixed with the calcined attapulgite to obtain a mixed recycled aggregate; A2. Fully mix metakaolin, quicklime and sodium carbonate to obtain a mixed powder; A3. The mixed recycled aggregate obtained in step A1, the mixed powder obtained in step A2, the silane coupling agent KH580 and water 1 are fully stirred and mixed, rammed and compacted, and after drying and solidification, they are allowed to stand and cure for not less than 7 days, and then crushed and sieved again to obtain a composite recycled aggregate with a particle size in the range of 4.75-13.2 mm.

[0008] By adopting the above technical solution, the preparation method of composite recycled aggregate is simple, and the cost of raw materials required is low, which is conducive to large-scale industrial production and pre-preparation, and can control the preparation cost to a certain extent, making the measures to improve the mechanical properties of concrete containing recycled aggregate more cost-effective. In addition, the particle size of the composite recycled aggregate is controlled within the range of 4.75-13.2mm. At this time, the composite recycled aggregate can be added to concrete as a coarse aggregate, which is conducive to improving the reinforcement effect of the composite recycled aggregate and thereby improving the mechanical properties of the concrete.

[0009] Optionally, in the step A1, the mass ratio of the recycled aggregate to the calcined attapulgite is 1:(0.5-0.75); in the step A2, the mass ratio of the metakaolin, the quicklime and the sodium carbonate is 1:(0.04-0.06):(0.1-0.12); in the step A3, the mass ratio of the mixed recycled aggregate, the mixed powder and the silane coupling agent KH580 is 200:60:3, and the mass ratio of the water I to the mixed powder is controlled to be (0.32-0.34):1.

[0010] By adopting the above technical scheme and controlling the mixing ratio between the raw materials, a composite recycled aggregate with a high degree of density and less harmful macroporous structure can be obtained, which is beneficial to further control the water absorption rate of the composite recycled aggregate, thereby reducing the impact of the addition of recycled aggregate on the mechanical properties of concrete, and is beneficial to further improve the performance of concrete containing recycled aggregate.

[0011] Optionally, the natural coarse aggregate is crushed stone with a particle size ranging from 4.75 to 13.2 mm, and the fine aggregate is natural river sand with a fineness modulus ranging from 2.6 to 3.1.

[0012] Optionally, the reinforcing fiber is at least one of polyvinyl alcohol fiber, polyacrylonitrile fiber or basalt fiber, and the length of the reinforcing fiber is 15-20 mm.

[0013] The above technical solution is helpful to improve the mechanical properties of concrete and enhance the durability of concrete. Secondly, when the reinforcing fiber is at this length, the concrete slurry can maintain a high fluidity and will not be affected by the excessively long fiber, which is beneficial to the application of concrete in the centrifugal molding process and is also beneficial to improve the crack resistance and bending resistance of the cement pole made of the concrete.

[0014] Optionally, the reinforcing fiber is a mixture of the polyvinyl alcohol fiber and the polyacrylonitrile fiber, and the mass ratio of the polyvinyl alcohol fiber to the polyacrylonitrile fiber is 1:(0.5-1).

[0015] By adopting the above technical solution, compared with adding a single fiber, the mixed addition of polyvinyl alcohol fiber and polyacrylonitrile fiber has a higher reinforcement and crack resistance effect, which is conducive to further improving the mechanical properties of concrete. In addition, since the cost of polyvinyl alcohol fiber is relatively low, it is conducive to controlling the cost of concrete, making the measures to improve the mechanical properties of concrete containing recycled aggregate more cost-effective.

[0016] Optionally, the reinforcing fiber needs to be surface treated before being added, wherein the surface treatment of the reinforcing fiber includes the following steps: First, the reinforcing fiber precursor is immersed in an acidic solution, heated to 55-60°C, fully stirred for reaction for 5-10 minutes, rinsed until the cleaning solution is neutral, and the acid-treated reinforcing fiber precursor is obtained. Then, the acid-treated reinforcing fiber precursor is immersed in a silane coupling agent KH560 solution for 20-30 minutes, taken out and dried, and then the length of the reinforcing fiber precursor is cut short to 15-20 mm, thereby completing the surface treatment of the reinforcing fiber.

[0017] By adopting the above technical solution, the surface treatment of the reinforcing fiber is beneficial to improve the compatibility and bonding strength between the reinforcing fiber and the concrete slurry, and further exert the reinforcing effect of the reinforcing fiber on the concrete, so that the reinforcing fiber can fully compensate for the adverse effects brought by the recycled aggregate and effectively improve the mechanical properties of the concrete.

[0018] Optionally, the composite water reducer is a mixture of a polycarboxylic acid-based high-performance water reducer and cellulose ether in a mass ratio of 1:(0.02-0.04), wherein the cellulose ether is any one of hydroxyethyl cellulose ether and hydroxypropyl methyl cellulose ether.

[0019] By adopting the above technical scheme, the water-cement ratio can be reduced, the mechanical strength of concrete can be improved, and the setting time of concrete can be appropriately prolonged, so that the concrete slurry can flow fully, which is beneficial to further improve the adaptability of the concrete slurry in the centrifugal forming process, so that the obtained concrete is more suitable for the production of cement poles.

[0020] In a second aspect, the present application provides a method for preparing a composite material concrete using the following technical solution: A method for preparing composite concrete comprises the following steps: S1. First, cement, fly ash, composite recycled aggregate, natural coarse aggregate and fine aggregate are fully dry-mixed at 150 r / min, and then a composite water reducer and 95% by weight of water II are added, and the stirring speed is maintained and continued to be stirred until the mixture reaches a flowable state, and then the stirring speed is increased to 250 r / min, and the stirring is continued to be uniform to obtain a first mixture; S2. While the first mixture is being stirred at high speed, reinforcing fibers and the remaining water II are added evenly in multiple times. After the reinforcing fibers are added, stirring is continued until the reinforcing fibers are evenly dispersed to obtain a composite material concrete.

[0021] By adopting the above technical solution, it is beneficial to fully mix the raw materials of concrete and obtain concrete slurry with good flowability and convenient centrifugal molding process. Secondly, the preparation method of concrete is simple and convenient, which is conducive to mass production and preparation.

[0022] In the third aspect, the present application provides a cement pole adopting the following technical solution: A cement pole is made of the composite material concrete and steel bars or steel wires through a centrifugal forming process.

[0023] In summary, the technical solution of this application has at least one of the following beneficial effects: 1. By compound modification of recycled aggregate and combining it with reinforcing fiber, under the same water-cement ratio, the adverse effects of recycled aggregate on concrete can be reduced to a certain extent, and the compressive strength of concrete can be effectively improved. At the same time, it is also beneficial to improve the crack resistance and bending resistance of cement poles made of the concrete. DETAILED DESCRIPTION

[0024] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0025] When purchasing cement, choose grade P.O42.5 silicate cement.

[0026] The fly ash was selected from Taiyue (Mining) Co., Ltd.

[0027] The polycarboxylic acid-based high-performance water reducer was specifically purchased from the PCA-I series of Jiangsu Subote New Materials.

[0028] The hydroxyethyl cellulose ether is specifically purchased from Dow Chemical's Hualuocell MT 400PFV.

[0029] The hydroxypropyl methylcellulose ether is specifically purchased from Dow Chemical's Hualuocell MC 40000.

[0030] Preparation Example [Preparation Example 1] A composite recycled aggregate is prepared by the following steps: A1. The waste concrete is fully crushed, cleaned, impurity-removed and sieved to obtain recycled aggregate with a particle size of less than 20 mm; the attapulgite is continuously calcined at 500° C. for 1 hour, and then the heating is stopped and the attapulgite is naturally cooled to room temperature to obtain calcined attapulgite; the recycled aggregate and the calcined attapulgite are fully mixed in a mass ratio of 1:0.5 to obtain mixed recycled aggregate; A2. Fully mix kaolin, quicklime and sodium carbonate in a mass ratio of 1:0.04:0.075 to obtain a mixed powder; A3. Take 400 kg of mixed recycled aggregate, 120 kg of mixed powder, 6 kg of silane coupling agent KH580 and 38.4 kg of water I, stir and mix them thoroughly, tamp and compact them, let them stand for 7 days after drying and solidification, then crush and sieve them again to obtain composite recycled aggregate with a particle size in the range of 4.75-13.2 mm.

[0031] [Preparation Example 2] A composite recycled aggregate is prepared by the following steps: A1. The waste concrete is fully crushed, cleaned, impurity-removed and sieved to obtain recycled aggregate with a particle size of less than 20 mm; the attapulgite is continuously calcined at 450° C. for 2 hours, and then the heating is stopped and the attapulgite is naturally cooled to room temperature to obtain calcined attapulgite; the recycled aggregate and the calcined attapulgite are fully mixed in a mass ratio of 1:0.75 to obtain mixed recycled aggregate; A2. Fully mix kaolin, quicklime and sodium carbonate in a mass ratio of 1:0.06:0.113 to obtain a mixed powder; A3. Take 400 kg of mixed recycled aggregate, 120 kg of mixed powder, 6 kg of silane coupling agent KH580 and 40.8 kg of water I, stir and mix them thoroughly, tamp and compact them, let them stand for 7 days after drying and solidification, then crush and sieve them again to obtain composite recycled aggregate with a particle size in the range of 4.75-13.2 mm.

[0032] [Preparation Example 3] A composite recycled aggregate, which is different from [Preparation Example 1] in that the mixed recycled aggregate is different.

[0033] In this preparation example, the mixed recycled aggregate is prepared by fully mixing the recycled aggregate and the calcined attapulgite in a mass ratio of 1:0.75.

[0034] [Preparation Example 4] A composite recycled aggregate, which is different from [Preparation Example 1] in that the particle size of the composite recycled aggregate is different.

[0035] In this preparation example, the composite recycled aggregate needs to be further crushed and sieved, and finally a composite recycled aggregate with a particle size of less than 1 mm is obtained.

[0036] [Preparation Example 5] A composite recycled aggregate, which is different from [Preparation Example 1] in that the composite recycled aggregate is different.

[0037] In this preparation example, the recycled aggregate is no longer mixed in the composite recycled aggregate, and the mixed recycled aggregate is replaced by recycled aggregate or the like.

[0038] Specifically, in step A3, 400 kg of recycled aggregate, 120 kg of mixed powder, 6 kg of silane coupling agent KH580 and 38.4 kg of water I are directly taken, fully stirred and mixed, tamped and compacted, and after drying and solidification, they are allowed to stand for 7 days, and then crushed and sieved again to obtain a composite recycled aggregate with a particle size in the range of 4.75-13.2 mm.

[0039] [Preparation Example 6] A composite recycled aggregate, which is different from [Preparation Example 1] in that the composite recycled aggregate is different.

[0040] In this preparation example, the mixed powder of metakaolin, quicklime and sodium carbonate is not added to the composite recycled aggregate.

[0041] Specifically, in step A3, 400 kg of mixed recycled aggregate, 6 kg of silane coupling agent KH580 and 38.4 kg of water I are directly taken, fully stirred and mixed, rammed and compacted, and after drying and solidification, they are allowed to stand for 7 days, and then crushed and sieved again to obtain a composite recycled aggregate with a particle size in the range of 4.75-13.2 mm. Example

[0042] [Example 1] A composite concrete comprising the following raw materials: The invention comprises the following raw materials in parts by weight: 300 kg of cement, 120 kg of fly ash, 500 kg of composite recycled aggregate, 750 kg of natural coarse aggregate, 550 kg of fine aggregate, 0.6 kg of reinforcing fiber, 3.06 kg of composite water reducing agent and 160 kg of water II.

[0043] Among them, the composite recycled aggregate is a composite recycled aggregate prepared in [Preparation Example 1], the natural coarse aggregate is natural crushed stone with a particle size in the range of 4.75-13.2 mm, the fine aggregate is natural river sand with a fineness modulus of 3.1, and the reinforcing fiber is polyvinyl alcohol fiber with a length of 20 mm.

[0044] The composite water reducer is specifically a mixture of a polycarboxylic acid-based high-performance water reducer and hydroxypropyl methylcellulose ether in a mass ratio of 1:0.02, that is, the composite water reducer includes 3 kg of polycarboxylic acid-based high-performance water reducer and 0.06 kg of hydroxypropyl methylcellulose ether.

[0045] A method for preparing composite concrete comprises the following steps: S1. First, cement, fly ash, composite recycled aggregate, natural coarse aggregate and fine aggregate are fully dry-mixed at a stirring speed of 150 r / min for 10 seconds, and then a composite water reducer and 95% by weight of water II are added, and the stirring speed is maintained and continued until the mixture reaches a flowable state, and then the stirring speed is increased to 250 r / min, and the stirring is continued for 5 minutes to obtain a first mixture; S2. While the first mixture is being stirred at high speed, reinforcing fibers and the remaining water II are added evenly in multiple times. After the reinforcing fibers are added, stirring is continued for 30 seconds so that the reinforcing fibers can be fully and evenly dispersed to obtain a composite material concrete.

[0046] The invention discloses an application method of composite material concrete, which can be combined with steel bars and made into cement poles through a centrifugal process, wherein the cement poles can be used as cement poles made of power transmission lines.

[0047] [Example 2] A composite concrete comprising the following raw materials: The invention comprises the following raw materials in parts by weight: 280 kg of cement, 160 kg of fly ash, 400 kg of composite recycled aggregate, 850 kg of natural coarse aggregate, 500 kg of fine aggregate, 1 kg of reinforcing fiber, 2.6 kg of composite water reducing agent and 180 kg of water II.

[0048] Among them, the composite recycled aggregate is a composite recycled aggregate prepared in [Preparation Example 2], the natural coarse aggregate is natural crushed stone with a particle size in the range of 4.75-13.2 mm, the fine aggregate is natural river sand with a fineness modulus of 2.8, and the reinforcing fiber is basalt fiber with a length of 15 mm.

[0049] The composite water reducer is specifically a mixture of a polycarboxylic acid high-performance water reducer and hydroxyethyl cellulose ether in a mass ratio of 1:0.04, that is, the composite water reducer includes 2.5 kg of polycarboxylic acid high-performance water reducer and 0.1 kg of hydroxyethyl cellulose ether.

[0050] A method for preparing composite concrete comprises the following steps: S1. First, cement, fly ash, composite recycled aggregate, natural coarse aggregate and fine aggregate are fully dry-mixed at a stirring speed of 150 r / min for 10 seconds, and then a composite water reducer and 95% by weight of water II are added, and the stirring speed is maintained and continued until the mixture reaches a flowable state, and then the stirring speed is increased to 250 r / min, and the stirring is continued for 5 minutes to obtain a first mixture; S2. While the first mixture is being stirred at high speed, reinforcing fibers and the remaining water II are added evenly in multiple times. After the reinforcing fibers are added, stirring is continued for 30 seconds so that the reinforcing fibers can be fully and evenly dispersed to obtain a composite material concrete.

[0051] The invention discloses an application method of composite material concrete, which can be combined with steel bars and made into cement poles through a centrifugal process, wherein the cement poles can be used as cement poles made of power transmission lines.

[0052] [Example 3] A composite material concrete, which is different from [Example 1] in that the composite recycled aggregate is different.

[0053] In this embodiment, the composite recycled aggregate is a composite recycled aggregate prepared in [Preparation Example 3].

[0054] [Example 4] A composite material concrete, which is different from [Example 1] in that the composite recycled aggregate is different.

[0055] In this embodiment, the composite recycled aggregate is a composite recycled aggregate prepared in [Preparation Example 4].

[0056] [Example 5] A composite material concrete, which differs from [Example 1] in that the reinforcing fibers are different.

[0057] In this embodiment, the reinforcing fiber is a mixture of polyvinyl alcohol fiber and polyacrylonitrile fiber in a mass ratio of 1:0.5, that is, the reinforcing fiber includes 0.4 kg of polyvinyl alcohol fiber and 0.2 kg of polyacrylonitrile fiber.

[0058] [Example 6] A composite material concrete, which differs from [Example 5] in that the reinforcing fibers are different.

[0059] In this embodiment, the reinforcing fiber is a mixture of polyvinyl alcohol fiber and polyacrylonitrile fiber in a mass ratio of 1:1, that is, the reinforcing fiber includes 0.3 kg of polyvinyl alcohol fiber and 0.3 kg of polyacrylonitrile fiber.

[0060] [Example 7] A composite material concrete, which differs from [Example 5] in that the reinforcing fibers are different.

[0061] In this embodiment, the reinforcing fiber is a mixture of basalt fiber and polyacrylonitrile fiber in a mass ratio of 1:1, that is, the reinforcing fiber includes 0.3 kg of basalt fiber and 0.3 kg of polyacrylonitrile fiber.

[0062] [Example 8] A composite material concrete, which differs from [Example 6] in that the reinforcing fibers are different.

[0063] In this embodiment, the reinforcing fiber needs to be surface treated before being added, wherein the surface treatment of the reinforcing fiber includes the following steps: First, the reinforcing fiber precursor is immersed in an acidic solution, heated to 60°C, fully stirred for reaction for 5 minutes, rinsed until the cleaning solution is neutral, and the acid-treated reinforcing fiber precursor is obtained. Then, the acid-treated reinforcing fiber precursor is immersed in a 2% silane coupling agent KH560 solution for 20 minutes. After being taken out and dried, the fiber precursor is cut to 20 mm in length, thereby completing the surface treatment of the reinforcing fiber.

[0064] The reinforcing fiber strands refer to fiber strands that have not been cut and have a certain length.

[0065] Comparative Example [Comparative Example 1] A concrete, which differs from [Example 1] in that no composite recycled aggregate is added.

[0066] In this comparative example, the composite recycled aggregate was replaced by natural aggregate in equal amounts.

[0067] [Comparative Example 2] A concrete, which differs from [Example 1] in that no composite recycled aggregate is added.

[0068] In this comparative example, the composite recycled aggregate was replaced by the recycled aggregate prepared in step A1 of [Preparation Example 1] in equal amounts.

[0069] [Comparative Example 3] A concrete, which is different from [Example 1] in that the composite recycled aggregate is different.

[0070] In this comparative example, the composite recycled aggregate is a composite recycled aggregate prepared in [Preparation Example 5].

[0071] [Comparative Example 4] A concrete, which is different from [Example 1] in that the composite recycled material is different.

[0072] In this comparative example, the composite recycled aggregate is a composite recycled aggregate prepared in [Preparation Example 6].

[0073] Performance test data 1. Concrete compressive strength test: refer to Section 7.1 of GB / T 4623-2014 Annular Concrete Pole for testing, and record the average compressive strength (MPa) of the composite concrete samples prepared in each embodiment and comparative example after curing for 28 days.

[0074] 2. Crack resistance test: The concrete prepared in each embodiment and comparative example is used in combination with steel bars to make cement poles, wherein the cement poles are straight poles, the reinforcement is 18 HRB400φ9.0, the size requirements are tip diameter 230mm, wall thickness 80mm, and length 15m, and then refer to Section 6.5 of "GB / T 4623-2014 Annular Concrete Pole" to perform cracking test bending moment and bearing capacity test bending moment, and record the corresponding crack width (mm) and pole top winding (mm). Among them, the cracking test bending moment needs to be loaded to 98.00kN·m, and the bearing capacity test bending moment needs to be loaded to 196.00kN·m.

[0075] Table 1 Mechanical properties test data of concrete and cement poles Combining Example 1 with Comparative Examples 1-4 and the data in Table 1, it can be seen that under the same water-cement ratio, Example 1 uses calcined attapulgite, metakaolin, quicklime, sodium carbonate and silane coupling agent to modify the recycled aggregate, and with a certain length of polyvinyl alcohol fiber, it can reduce the adverse effects of recycled aggregate on concrete to a certain extent, effectively improve the compressive strength of concrete, and further improve the crack resistance and bending resistance of cement poles made of the concrete. This may be because after calcining the attapulgite, the content of active silica in the attapulgite increases, and the cementitious material produced by the metakaolin, quicklime and sodium carbonate in water can fully absorb and combine to fill the pores inside and outside the recycled aggregate, which is beneficial to improve the shrinkage, water absorption rate and pore structure of the recycled aggregate, not only improve its compatibility with the concrete paddle, but also reduce the harmful macroporous structure in the concrete, which is beneficial to improve the density of the concrete, and thus improve the mechanical properties of the concrete and cement poles.

[0076] Combining Example 1 with Example 3 and the data in Table 1, it can be seen that as the proportion of calcined attapulgite in the composite recycled aggregate increases, although the compressive strength of the concrete increases to a certain extent, the top winding of the prepared cement pole increases, and when the bearing capacity is tested for bending moment, the crack width increases, indicating that the crack resistance and bending resistance of the cement pole decrease, the stiffness of the cement pole decreases, and it is more likely to cause stress concentration or crack expansion caused by external loads. This may be due to the strong water absorption of calcined attapulgite. As the proportion increases, the effective water-binder ratio in the composite recycled aggregate will further decrease, making the mixture difficult to vibrate, which will directly affect the density and void structure of the composite recycled aggregate, and may reduce the water absorption rate modification effect of the composite recycled aggregate, and affect the mechanical properties of concrete and cement poles.

[0077] Combining Example 1 with Example 4 and the data in Table 1, it can be seen that when the particle size of the composite recycled aggregate is further crushed to a particle size of less than 1 mm, the composite recycled aggregate is added to the concrete as fine aggregate, and the compressive strength of the concrete decreases slightly, but the winding and crack width of the cement pole increase significantly, indicating that its crack resistance and bending resistance decrease. This may be because after the composite recycled aggregate is further crushed to a particle size of less than 1 mm, the specific surface of the composite recycled aggregate is greatly increased, and more cement slurry is required for wetting. When the water-cement ratio of Example 1 and Example 4 is the same, too much fine aggregate may cause the fluidity of the concrete to decrease, thereby reducing the compactness and mechanical strength of the concrete.

[0078] Combining Example 1 with Examples 5-7 and the data in Table 1, it can be seen that when the reinforcing fiber is a mixture of polyvinyl alcohol fiber and polyacrylonitrile fiber in a mass ratio of 1:1, the reinforcing fiber can further improve the reinforcing effect of the mechanical strength of concrete compared to the addition of polyvinyl alcohol fiber alone. In addition, when the polyvinyl alcohol fiber is replaced with basalt fiber of equal length, the performance of the concrete does not change much, but since the cost of polyvinyl alcohol fiber is relatively low, it is more cost-effective to select a mixture of polyvinyl alcohol fiber and polyacrylonitrile fiber.

[0079] Combining Example 1 with Example 8 and the data in Table 1, it can be seen that after surface treatment of the reinforcing fiber, the mechanical strength of the concrete can also be further improved, so that the cement pole has better compressive strength, crack resistance and bending resistance. This may be because after the reinforcing fiber is treated with acid and modified with a coupling agent, the compatibility and bonding strength between the reinforcing fiber and the concrete are further improved, and the reinforcing effect of the reinforcing fiber can be further exerted, thereby fully improving the compressive strength, crack resistance and bending strength of the concrete to compensate for the adverse effects of the recycled aggregate.

[0080] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A composite material concrete, characterized in that: It includes the following raw materials in parts by weight: Cement: 280-300 parts; Fly ash: 120-160 parts; Composite recycled aggregate: 400-500 parts; Natural coarse aggregate: 750-850 parts; Fine aggregate: 500-550 parts; Reinforcing fiber: 0.6-1 part; Composite water reducing agent: 2.6-3.04 parts; Water II: 160-180 parts; The composite recycled aggregate is prepared by mixing and modifying recycled aggregate with calcined attapulgite, metakaolin, quicklime, sodium carbonate and silane coupling agent, and the recycled aggregate is obtained by crushing and screening waste concrete.

2. The composite material concrete according to claim 1, characterized in that: The preparation method of the composite recycled aggregate comprises the following steps: A1. The waste concrete is fully crushed, cleaned, impurity-removed and sieved to obtain a recycled aggregate with a particle size of less than 20 mm; the attapulgite is continuously calcined at 450-500° C. for 1-2 hours, and then the heating is stopped and the attapulgite is naturally cooled to room temperature to obtain calcined attapulgite; the recycled aggregate is fully mixed with the calcined attapulgite to obtain a mixed recycled aggregate; A2. Fully mix metakaolin, quicklime and sodium carbonate to obtain a mixed powder; A3. The mixed recycled aggregate obtained in step A1, the mixed powder obtained in step A2, the silane coupling agent KH580 and water 1 are fully stirred and mixed, rammed and compacted, and after drying and solidification, they are allowed to stand and cure for not less than 7 days, and then crushed and sieved again to obtain a composite recycled aggregate with a particle size in the range of 4.75-13.2 mm.

3. A composite material concrete according to claim 2, characterized in that: In the step A1, the mass ratio of the recycled aggregate to the calcined attapulgite is 1:(0.5-0.75); in the step A2, the mass ratio of the metakaolin, the quicklime and the sodium carbonate is 1:(0.04-0.06):(0.1-0.12); in the step A3, the mass ratio of the mixed recycled aggregate, the mixed powder and the silane coupling agent KH580 is 200:60:3, and the mass ratio of the water I to the mixed powder is controlled to be (0.32-0.34):

1.

4. The composite material concrete according to claim 1, characterized in that: The natural coarse aggregate is crushed stone with a particle size ranging from 4.75 to 13.2 mm, and the fine aggregate is natural river sand with a fineness modulus ranging from 2.6 to 3.

1.

5. The composite material concrete according to claim 1, characterized in that: The reinforcing fiber is at least one of polyvinyl alcohol fiber, polyacrylonitrile fiber or basalt fiber, and the length of the reinforcing fiber is 15-20 mm.

6. The composite material concrete according to claim 5, characterized in that: The reinforcing fiber is a mixture of the polyvinyl alcohol fiber and the polyacrylonitrile fiber, and the mass ratio of the polyvinyl alcohol fiber to the polyacrylonitrile fiber is 1:(0.5-1).

7. The composite material concrete according to claim 5, characterized in that: The reinforcing fiber needs to be surface treated before adding, wherein the surface treatment of the reinforcing fiber includes the following steps: First, the reinforcing fiber precursor is immersed in an acidic solution, heated to 55-60°C, fully stirred for reaction for 5-10 minutes, rinsed until the cleaning solution is neutral, and the acid-treated reinforcing fiber precursor is obtained. Then, the acid-treated reinforcing fiber precursor is immersed in a silane coupling agent KH560 solution for 20-30 minutes, taken out and dried, and then the fiber precursor is cut to 15-20 mm in length, thereby completing the surface treatment of the reinforcing fiber.

8. The composite material concrete according to claim 1, characterized in that: The composite water reducer is a mixture of a polycarboxylic acid-based high-performance water reducer and cellulose ether in a mass ratio of 1: (0.02-0.04), wherein the cellulose ether is any one of hydroxyethyl cellulose ether and hydroxypropyl methyl cellulose ether.

9. A method for preparing a composite material concrete, used for preparing a composite material concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. First, cement, fly ash, composite recycled aggregate, natural coarse aggregate and fine aggregate are fully dry-mixed, and then a composite water reducer and 95% by weight of water II are added, and the stirring speed is maintained and continued to be stirred until the mixture reaches a flowable state, and then the stirring speed is increased and continued to be stirred evenly to obtain a first mixture; S2. While the first mixture is being stirred at high speed, reinforcing fibers and the remaining water II are added evenly in multiple times. After the reinforcing fibers are added, stirring is continued to be evenly performed to obtain a composite material concrete.

10. A cement pole, characterized in that: The composite material concrete according to any one of claims 1 to 8 is made by a centrifugal forming process with steel bars or steel wires.

Citation Information

Cited By

  • Early-strength and durable concrete for cement poles and preparation method thereof

    CN122725764A